Cytotoxic and genotoxic effects of extracts from Annona montana M. fruit - Bailon Moscoso, N. (2016)
Pulverized immature fruits of Annona montana M. are commonly used for biomedical applications, especially in the treatment of dysentery. The aim of this study was to investigate whether hexane, ethyl acetate or methanol extracts of A. montana M. can be cytotoxic to human tumor cells or exhibit genotoxic effects on normal human cells. The organic extracts were shown to inhibit survival of tumor cells originating from human astrocytoma, breast, colon, lung and prostate cancers. Furthermore, they were found to induce DNA damage in normal human lymphocytes, as shown by comet assay. The genotoxic effects observed suggest that traditional folk medicines prepared from extracts of the immature fruit of A. montana should be used with caution.